Performance and Emissions of Vehicle Fueled with Different Blend of Euro 5 Biodiesel - Aimi, Nurjihan binti; Mohd Ali, Mas Fawzi (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Biodiesel is gaining attention of the world nowadays due to the availability of sources and its renewable fuel. As an alternative fuel, biodiesel fuel has many advantages to help improve the environment. Palm Oil is one of the vegetable oils that has the potential to be used as fuel in diesel engines. The concept of different blends of palm oil biodiesel B10, B20 and, B30, 30% biodiesel, and 70% diesel in this study were used to evaluate engine performance and emission after reach 50,000 km. Dynamometer tests were conducted to obtain the performance of engines fuelled with B10, B20 and B30. The B30 fuel produces the lowest engine performance of torque and power while the B10 records the highest. The BSFC and BTE for B30 are higher compared to B20. Thus, engine emissions for B30 show lower amount of CO2, CO, smoke opacity, and soot than B20 but has an increase in NOx and O2 emissions. After the vehicle test using B30 fuel and after reach 50,000 km, it was found that there was no significant change in engine performance and emission.